Integrative taxonomy resolves three new cryptic species of small southern African horseshoe bats (Rhinolophus). Issue 4 (24th April 2018) - Taylor, Peter J; Macdonald, Angus; Goodman, Steven M; Kearney, Teresa; Cotterill, Fenton P D; Stoffberg, Sam; Monadjem, Ara; Schoeman, M Corrie; Guyton, Jennifer; Naskrecki, Piotr; Richards, Leigh R
Abstract: Examination of historical and recent collections of small Rhinolophus bats revealed cryptic taxonomic diversity within southern African populations previously referred to as R . swinnyi Gough, 1908 and R . landeri Martin, 1832. Specimens from Mozambique morphologically referable to R . swinnyi were phylogenetically unrelated to topotypic R . swinnyi from the Eastern Cape Province of South Africa based on cytochrome b sequences and showed distinctive echolocation, baculum and noseleaf characters. Due to their genetic similarity to a previously reported molecular operational taxonomic unit (OTU) from north-eastern South Africa, Zimbabwe and Zambia, we recognize the available synonym ( R . rhodesiae Roberts, 1946) to denote this distinct evolutionary species. This new taxon is genetically identical to R. simulator K. Andersen, 1904 based on mtDNA and nuclear DNA sequences but can easily be distinguished on morphological and acoustic grounds. We attribute this genetic similarity to historical introgression, a frequently documented phenomenon in bats. An additional genetically distinct and diminutive taxon in the swinnyi s.l. group (named herein, R . gorongosae sp. nov. ) is described from Gorongosa National Park, central Mozambique. Specimens from Mozambique referable based on morphology to R . landeri were distinct from topotypic landeri from West Africa based on mtDNA sequences, and acoustic, noseleaf and baculum characters. This Mozambique population is assigned to the available synonym R . lobatus Peters, 1952.